Peran Kepemimpinan Dalam Manajemen Perubahan Di Dalam Organisasi - Ayu Intan Pratiwi; Nuri Aslami (LPPM Universitas Labuhanbatu, 2023)
Organizations are social structures that are coordinated across national boundaries and work to achieve organizational goals. Leadership is one of the keys to the success of an organization in responding to these changes, and through planning and implementing organizational change, leadership plays a role in determining the direction of organizational change. Strong leadership is needed through management actions to influence and guide organizational members to achieve change. Transformative leadership is a modification of charismatic leadership because it can create a strong emotional connection with the community to achieve certain goals. The purpose of this study is to explain the role of leadership in change management for an organization. The method used is a qualitative research method. The result of this research is the importance of leadership in change management. Change must be designed, designed, and managed by strong, positive, intelligent and growing leadership.